Phospholipid Metabolism During Changes in the Proportions of Membrane-bound Respiratory Pigments in Haemophilus parainfluenzae - White, David C. (1969)
After a transition from high to low oxygen tension, there was a twofold to 50-fold increase in the content of membrane-bound respiratory pigments of Haemophilus parainfluenzae, and there were concurrent changes in the metabolism of the membrane phospholipids: (i) a twofold decrease in the rate of turnover of the phosphate in all the phospholipids; (ii) a shift from simple one-phase, linear incorporation of phosphate into phospholipids to a complex biphasic incorporation of phosphate into phospholipids; and (iii) an increase in the total phospholipids with a slight increase in the proportion of phosphatidylglycerol (PG) and a slight decrease in the proportion of phosphatidylethanolamine (PE). Changes in the rates of incorporation of phosphate into the phospholipids occurred without a change in the rate of bacterial growth. When the compensatory adjustment of the proportions of the respiratory pigments reached a steady state, the total phospholipid, the rate of incorporation of phosphate into phospholipids, and the proportion of PG fell. At steady-state proportions of cytochromes, the proportion of PE and the rate of turnover of the phosphate in the phospholipids increased. All through an incorporation experiment of 1.5 divisions, the specific activity of the phosphate of PG was twice that of phosphatidic acid (PA). The phosphate of PG turned over 1.2 to 1.5 times more rapidly than the phosphate of PA in cells with high and low cytochrome levels. If the PA was an accurate measure of the precursor for the cytidine-5′-diphosphate-diglyceride, which in turn was the precursor of all the lipids, then the results of these experiments suggested that exchange reactions, in addition to synthesis from PA, were involved in phospholipid metabolism. These reactions were more sensitive to changes in oxygen concentration than was the growth rate.